Optical characterization of Ba0.5Sr0.5TiO3 material grown on a p-type silicon substrate (111) doped niobium oxide and chlorophyll. Issue 1 (17th November 2020) - Setiawan, Aep; Palupi, Endah Kinarya; Umam, Rofiqul; Alatas, Husin; Irzaman,
Abstract: Barium Strontium Titanate (BST) is a material that has a dielectric constant and high load storage capacity. BST is made with 3 variations namely BST without container, BST in Niobium Oxide container, and BST in chlorophyll container. Percentage of container mass is 5% and 10% of BST mass. The method used is Chemical Solution Deposition (CSD). The process of growing thin films is done using Spin Coating with a speed of 3000 rpm for 30 seconds. The dropping process is carried out 3 times. The BST was turned at 850 °C for 22 hours of detention. The XRD characterization results showed that there was no structural shift from the BST that was made, this was seen from the lattice parameter values ​​obtained, namely 4.07Ǻ for BST, 4.07Ǻ for BST at 5% niobium oxide, 4.07Ǻ for BST at 10% niobium oxide, 4.06 Ǻ BST was taken by 5% chlorophyll, and 4.08 ST BST was taken by 10% chlorophyll. Characterization of optical properties showed that the addition of niobium oxide and chlorophyll reservoirs caused the absorbance of BST to decrease, the refractive index value to increase, and the gap energy value to decrease. Gap energy value is 2.23 eV at BST at 5% niobium oxide, 2.05 eV at BST at 10% niobium oxide, 2.46 eV at BST at 5% chlorophyll, and 2.47 eV at BST at 10% chlorophyll, where the energy gap value is based on literature 3.45 eV.